Data from: The loss of hemoglobin and myoglobin does not minimize oxidative stress in Antarctic icefishes - O'Brien, Kristin M.; Crockett, Elizabeth L.; Philip, Jacques; Oldham, Corey A.; Hoffman, Megan; Kuhn, Donald E.; Barry, Ronald; McLaughlin, Jessica (2017)
The unusual pattern of expression of hemoglobin (Hb) and myoglobin (Mb) among Antarctic notothenioid fishes provides an exceptional model system for assessing the impact of these proteins on oxidative stress. We tested the hypothesis that the lack of oxygen-binding proteins may reduce oxidative stress. Levels and activity of pro-oxidants, small-molecule and enzymatic antioxidants, and levels of oxidized lipids and proteins in liver, oxidative skeletal muscle, and heart ventricle were quantified in five species of notothenioid fishes differing in the expression of Hb and Mb. Levels of ubiquitinated proteins and rates of protein degradation by the 20S proteasome were also quantified. Although levels of oxidized proteins and lipids, ubiquitinated proteins, and antioxidants are higher in red-blooded fishes than in Hb-less icefishes in some tissues, this pattern does not persist across all tissues. Expression of Mb is not associated with oxidative damage in heart ventricle, whereas the activity of citrate synthase and contents of heme are positively correlated with oxidative damage in most tissues. Despite some tissue differences in levels of protein carbonyls among species, rates of degradation by the 20S proteasome are not markedly different, suggesting either alternative pathways for eliminating oxidized proteins or redox tone varies among species. Together, our data indicate that the loss of Hb and Mb does not correspond with a clear pattern of either reduced oxidative defense or oxidative damage. Data Summary JEB O'Brien et al JEXBIO_2017_162503